1996
DOI: 10.1002/(sici)1097-4660(199604)65:4<370::aid-jctb445>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Detoxification of 2-Chloroethyl Ethyl Sulfide

Abstract: Rhodococcus rhodochrous IGTS8 (ATCC 53968) was shown to be capable of utilizing 2-chloroethyl ethyl sulphide (CEES) as the sole source of sulphur for microbial growth. 2-Chloroethanol and a compound tentatively identified as 2-chloroethanesulfinic acid have been detected as metabolites. This demonstrates that carbon-sulphur bonds were cleaved in CEES prior to hydrolysis of the chlorine atom. These data indicate that Rhodococcus rhodochrous IGTSS may be useful for the biodetoxification of the chemical warfare a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Van Hamme et al (45) have shown that a variety of white-rot fungi oxidize dibenzyl sulfide to dibenzyl sulfoxide and dibenzyl sulfone prior to further degradation. However, other examples of the microbial degradation of compounds containing this type of bond (e.g., 2-chloroethyl sulfide and thiodiglycol) give no evidence for direct sulfur oxidation followed by COS bond cleavage without degradation of the alkyl or aromatic moieties (20,29,36,40). For example, metabolism by Nocardioides simplex of 1-(phytanylsulfanyl)-octadecane (used as a model compound for sulfide bridges in high-molecular-weight fractions of sulfur-rich petroleum) has been described previously (18); although the sulfur was oxidized, no COS bond cleavage was observed.…”
mentioning
confidence: 99%
“…Van Hamme et al (45) have shown that a variety of white-rot fungi oxidize dibenzyl sulfide to dibenzyl sulfoxide and dibenzyl sulfone prior to further degradation. However, other examples of the microbial degradation of compounds containing this type of bond (e.g., 2-chloroethyl sulfide and thiodiglycol) give no evidence for direct sulfur oxidation followed by COS bond cleavage without degradation of the alkyl or aromatic moieties (20,29,36,40). For example, metabolism by Nocardioides simplex of 1-(phytanylsulfanyl)-octadecane (used as a model compound for sulfide bridges in high-molecular-weight fractions of sulfur-rich petroleum) has been described previously (18); although the sulfur was oxidized, no COS bond cleavage was observed.…”
mentioning
confidence: 99%
“…The results with acetonitrile, a toxic compound with poor biokinetic properties, further suggest that drip-feed biotreatment would offer a safe alternative for the treatment of other highly toxic, but biodegradable substances, such as sarin, VX, and mustard (Kilbane and Jackowski 1996, Lee et al 1996, Shem et al 1995. Challenges facing the safe disposal of chemical warfare materiel (CWM) is similar to the challenges facing the safe disposal of mixed wastes.…”
Section: Drip-feed Bioreactor Operationmentioning
confidence: 99%
“…Biological treatment of mustard and mustard hydrolysis products have been demonstrated (Kilbane and Jackowski 1996, Lee et al 1996, NRC 2000, NRC 2002, Shem et al 1995, but projects examining the biological treatment of nerve agents have failed due to poor bioreactor design (NRC 2000). Novel reactor configurations, such as the drip-feed bioreactor, could offer practical alternatives to the disposal of difficult to handle waste streams.…”
Section: Drip-feed Bioreactor Operationmentioning
confidence: 99%
“…There are comparatively few reports of the degradation of aliphatic sulfides, particularly of carbon-sulfur bond cleavage in high molecular weight representatives of this class of compound. Small compounds, including methyl, ethyl, propyl and butyl sulfides Taylor 1993a, 1993b), 2-chloroethyl ethyl sulfide (Kilbane and Jackowski 1996) and thiodiglycol (Lee et al 2001), are cleaved at the sulfur atom. The latter two compounds were used to investigate the potential for biological treatment of the chemical warfare agent sulfur mustard (2,2¢-dichlorodiethyl sulfide).…”
Section: Introductionmentioning
confidence: 99%